Welding and distortion control(sach pho to coppy) - R Mandal N (Alpha Science International, 2004)
Welding is one of the major and principal activities in today's shipbuilding and offshore industry. The performance of these industries as regards productivity, meeting delivery schedule, product quality, etc.depends very much on the structure designs and welding technology adopted in these yards as well as the distortion control measures implemented during fabrication. It may be of interest to note here that whether it is a ship or an offshore structure, huge subassembiles and assemblies are put together to get the final product. In the entire process, welding plays a very important role as far as productivity and quality of the end product is concerned.